Tracking novel adenovirus in environmental and human clinical samples: no evidence of endemic human adenovirus type 58 circulation in Córdoba city, Argentina - Ferreyra, L. J. (2014)
In recent years, several types of human adenovirus (HAdV) have arisen from the recombination between two or more previously known HAdV types, but their epidemiology is poorly understood. In this study, we investigated the circulation of HAdV-58, a recently described HAdV isolated from an HIV-positive patient in Córdoba city, Argentina. For this purpose, a 30-month survey was conducted to study the presence of this type of adenovirus in sewage samples collected at the inlet from a wastewater treatment plant in Córdoba city, Argentina. Complementarily, the virus was sought in stools of HIV-positive patients. Although HAdVs were detected in human stool samples and in a high percentage of sewage samples, no evidence of HAdV-58 circulation was detected. We suggest that there is no endemic circulation of HAdV-58 in the geographical local area. The trend is that the number of identified HAdVs increases over time. In this context, understanding the current circulating HAdVs may be biologically relevant.